2022
DOI: 10.1109/jstars.2022.3152904
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scenario Simulation of Land Use for Sustainable Development Goals

Abstract: Considering the UN sustainable development goals (SDGs) released in 2015, this article constructed an SDGoriented land use simulation (SDG-LUS) model incorporating SDG-oriented system dynamics (SDG-SD) and SDG-oriented cellular automata (SDG-CA), and utilized it to simulate land use changes in the Yangtze river delta region. The SDG-SD model was developed to predict the land use demands from 2021 to 2030 under the constraints of multiple SDG indicators, including economic indicators (SDG2.3.1 and SDG8.1.1), so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The coupled investigation of land use and land cover in monitoring land-use efficiency in Europe showed that between 2012 and 2018, the number of countries moving towards efficient land use doubled, compared to the period 2006-2012 [28], revealing that notable progress towards achieving SDG 11.3.1 [29] was reported in such developed and highly industrialized countries as Portugal and Germany, while almost all the Balkan countries also moved towards more efficient land use [28]. This research trend implies the validity and the applicability of the SDG-land use simulations, scenarios and models, confirming that these scenario simulations of different sustainability levels are conducive to supporting the formulation of sustainable land-use plans covering almost any region of Earth [29][30][31][32][33][34][35], while plentiful studies have also reported on other European contexts [36][37][38].…”
Section: Land Use and Land Cover Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coupled investigation of land use and land cover in monitoring land-use efficiency in Europe showed that between 2012 and 2018, the number of countries moving towards efficient land use doubled, compared to the period 2006-2012 [28], revealing that notable progress towards achieving SDG 11.3.1 [29] was reported in such developed and highly industrialized countries as Portugal and Germany, while almost all the Balkan countries also moved towards more efficient land use [28]. This research trend implies the validity and the applicability of the SDG-land use simulations, scenarios and models, confirming that these scenario simulations of different sustainability levels are conducive to supporting the formulation of sustainable land-use plans covering almost any region of Earth [29][30][31][32][33][34][35], while plentiful studies have also reported on other European contexts [36][37][38].…”
Section: Land Use and Land Cover Considerationsmentioning
confidence: 99%
“…In the relevant literature there are numerous studies devoted to land use and sustainable development, especially considering the published United Nations Sustainable Development Goals (SDGs), showing a wider geographical, practical and management pluralism [29,51,62,73,74]. Researchers have also argued that while conventional instruments for land-use planning have been increasingly criticized, economic instruments (including taxes, subsidies and tradeable permits) in the context of land-use steering have received growing attention in practice and research [75].…”
Section: Key Aspects and Considerations On The Jointly Reported "Land...mentioning
confidence: 99%
See 1 more Smart Citation
“…Land is the main element of the natural environmental substrate and is an important carrier of socio-economic development [5]. Furthermore, the rational use and management of land is a crucial way to resolve socio-economic conflicts and contribute to the harmonization of environment, society, and economy [6]. In addition, the SDGs will thoroughly address the development of the three dimensions of society, economy, and environment in an integrated manner between 2015 and 2030 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The economic losses amount to approximately 35.3 billion euros (https://us.milli man.com/-/media/ milli man/ pdfs/2022-artic les/3-28-22_europ e-extre me-weath er-report.ashx). Therefore, it is significant to carry out research on flood-related issues for improving disaster resilience in cities and meeting the challenges associated with the SDGs on Sustainable Cities and Communities (Cao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%